Results for the B-meson decay constant from the APE collaboration - Chris Allton (Nuclear Physics B - Proceedings Supplements, 1995)
The decay constant for the B-meson in the static limit is calculated using the Wilson and clover actions at various lattice spacings. We show that both the contamination of our results by excited states and the effects finite lattice spacing are at most the order of the statistical uncertainties. A comparison is made of our results and those obtained in other studies. Values for $f~{stat}_{B_S}/f~{stat}_B$ and $M_{B_S} - M_B$ are also given.